Combined proteomic and lipidomic studies in Pompe disease allow a better disease mechanism understanding. Issue 3 (28th December 2020) - Sidorina, Anna; Catesini, Giulio; Levi Mortera, Stefano; Marzano, Valeria; Putignani, Lorenza; Boenzi, Sara; Taurisano, Roberta; Garibaldi, Matteo; Deodato, Federica; Dionisi‐Vici, Carlo
Abstract: Pompe disease (PD) is caused by deficiency of the enzyme acid α‐glucosidase resulting in glycogen accumulation in lysosomes. Clinical symptoms include skeletal myopathy, respiratory failure, and cardiac hypertrophy. We studied plasma proteomic and lipidomic profiles in 12 PD patients compared to age‐matched controls. The proteomic profiles were analyzed by nLC‐MS/MS SWATH method. Wide‐targeted lipidomic analysis was performed by LC‐IMS/MS, allowing to quantify >1100 lipid species, spanning 13 classes. Significant differences were found for 16 proteins, with four showing the most relevant changes (GPLD1, PON1, LDHB, PKM). Lipidomic analysis showed elevated levels of three phosphatidylcholines and of the free fatty acid 22:4, and reduced levels of six lysophosphatidylcholines. Up‐regulated glycolytic enzymes (LDHB and PKM) are involved in autophagy and glycogen metabolism, while down‐regulated PON1 and GPLD1 combined with lipidomic data indicate an abnormal phospholipid metabolism. Reduced GPLD1 and dysregulation of lipids with acyl‐chains characteristic of GPI‐anchor structure suggest the potential involvement of GPI‐anchor system in PD. Results of proteomic analysis displayed the involvement of multiple cellular functions affecting inflammatory, immune and antioxidant responses, autophagy, Ca 2+ ‐homeostasis, and cell adhesion. The combined multi‐omic approach revealed new biosignatures in PD, providing novel insights in disease pathophysiology with potential future clinical application. Abstract :